2021
DOI: 10.3389/fped.2021.727362
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Nomogram for Moderate-to-Severe Bronchopulmonary Dysplasia or Death: Role of N-Terminal Pro-brain Natriuretic Peptide as a Biomarker

Abstract: Objectives: This study aimed to explore the clinical value of N-terminal pro-brain natriuretic peptide (NT-proBNP) in predicting moderate-to-severe bronchopulmonary dysplasia (BPD)/death, and to establish an effective clinical predictive nomogram.Methods: We retrospectively analyzed very low birth weight infants (VLBWs) with gestational age ≤ 32 weeks. The NT-proBNP values were determined on the 1st, 3rd, 7th, 14th, 21st, and 28th days after birth. The correlation between NT-proBNP level and moderate-to-severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 57 publications
(56 reference statements)
1
25
0
Order By: Relevance
“…Our prospective study demonstrated that the urine NT-proBNP concentrations were significantly elevated from DOL 7 to 28 in preterm infants who, many weeks later, developed BPD (P < 0.05). This result linked circulatory stress to BPD in the first 4 weeks of life for preterm infants and were consistent with serum NT-proBNP level trends reported by Song et al (33). We also found that urine NT-proBNP levels from DOL 7 to 28 positively correlated with mechanical ventilation duration and oxygen exposure time.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our prospective study demonstrated that the urine NT-proBNP concentrations were significantly elevated from DOL 7 to 28 in preterm infants who, many weeks later, developed BPD (P < 0.05). This result linked circulatory stress to BPD in the first 4 weeks of life for preterm infants and were consistent with serum NT-proBNP level trends reported by Song et al (33). We also found that urine NT-proBNP levels from DOL 7 to 28 positively correlated with mechanical ventilation duration and oxygen exposure time.…”
Section: Discussionsupporting
confidence: 92%
“…Prenatal exposure to oxidative stress, postnatal hyperoxia, and prolonged mechanical ventilation may increase pulmonary vascularization damage by modulating vascular tone ( 34 ). Elevated serum NT-proBNP levels may be related to raised pulmonary vascular pressure and diastolic dysfunction ( 33 , 35 ). Our study discovered a persistently positive correlation between an oxidative stress-related biomarker (i.e., 8-OHdG) and NT-proBNP levels in urine from DOL 7 to 28 (r: 0.655–0.789, P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…The dynamics and values of NT‐proBNP levels are similar in premature infants compared with healthy term infants, reaching stable plateau values after the first month of life 30,31 . The pCA and prematurity related comorbidities (BPD and hs‐PDA) seem to affect NT‐proBNP concentrations more than the GA, but their influence is rarely present after a pCA of >36 weeks 28–32 . Therefore, our small sample size including infants with a median pCA of 46 +1 weeks, 4 premature infants all with pCA >36 weeks, and only 1 patient with BPD could explain our unexpected results.…”
Section: Discussionmentioning
confidence: 94%
“…The plasmatic concentration of NT-proBNP in infants is clearly influenced by the chronological age, prematurity, and its related complications (BPD, hs-PDA, …). 17,[28][29][30][31][32] As all these variables are wellknown risk factors for worse outcomes in acute bronchiolitis, their influence on NT-proBNP concentrations should be considered before stablishing the use of this biomarker in this setting. In our exploratory analysis the urinary NT-proBNP levels resulted not associated with any of these parameters.…”
Section: Influence Of Clinical Variables On Urinary Nt-probnp Levelsmentioning
confidence: 99%
“…Different multicentre studies have demonstrated that the LUS score is also a good predictor of msBPD in children born before 32 weeks after the rst 3-7 DOLs [17,18,31]. In addition, NT-proBNP is related to msBPD prediction in the rst DOLs[8, 29,32], even after adjusting for haemodynamically signi cant PDA [7,8], and it remains related to pulmonary hypertension in preterm infants with BPD [33,34].…”
Section: Discussionmentioning
confidence: 99%